2006
DOI: 10.1111/j.1745-459x.2006.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Profiles of the Most Common Salmon Products on the Danish Market

Abstract: The sensory profiles of the most common chilled and frozen salmon products available to consumers on the Danish market were studied. A sensory profiling was made on 12 salmon products varying in salmon species, origin, storage method and time. Samples stored in ice between 7 and 16 days, frozen for 1 month or stored in modified atmosphere for 5 days all had sensory profiles dominated by sea/seaweed odor, juicy and oily texture, fresh fish oil, and sweet and mushroom flavor. Marked differences in the sensory pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…This probably explains the lower liking scores for the samples with long storage time compared to those with a short storage time. The sensory characteristics of ice stored salmon (Salmo salar) do not change much during the first 2 weeks of storage (Sveinsdóttir et al, 2002(Sveinsdóttir et al, , 2003Green-Petersen et al, 2006). However, at the end of shelf life sour, rancid, amine, and musty odor; sour, amine, and rancid flavor; and discoloration is evident (Sveinsdóttir et al, 2002(Sveinsdóttir et al, , 2003.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…This probably explains the lower liking scores for the samples with long storage time compared to those with a short storage time. The sensory characteristics of ice stored salmon (Salmo salar) do not change much during the first 2 weeks of storage (Sveinsdóttir et al, 2002(Sveinsdóttir et al, , 2003Green-Petersen et al, 2006). However, at the end of shelf life sour, rancid, amine, and musty odor; sour, amine, and rancid flavor; and discoloration is evident (Sveinsdóttir et al, 2002(Sveinsdóttir et al, , 2003.…”
Section: Resultsmentioning
confidence: 98%
“…The reason might be the differences between the species and also the prolonged frozen storage (Table 1). In an earlier experiment, sensory characteristics of Salmo salar, Oncohynchus keta, and Oncohynchus kisutch were compared (Green-Petersen et al, 2006) by using a trained sensory panel. Here it was found that the samples of Oncohynchus keta were not particularly different from the samples of Salmo salar, while the sample of Oncohynchus kisutch showed a greater difference to the Salmo salar.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…for odour/flavour: sea/seaweed, sweet, cooked potato, warm milk, cucumber, • fresh fish oil, mushroom for texture: juicy, oily and firm (Green-Petersen • et al ., 2006;Hyldig, 2009Hyldig, , 2010Sveinsdóttir et al ., 2010).…”
Section: Ice Storagementioning
confidence: 99%